2013
DOI: 10.1186/1477-7819-11-130
|View full text |Cite
|
Sign up to set email alerts
|

The value of chest CT for prediction of breast tumor size: comparison with pathology measurement

Abstract: BackgroundLittle information is available on the use of chest computed tomography (CT) to predict breast tumor size in breast cancer, despite the fact that chest CT examinations are being increasingly used. The purpose of this study was to evaluate the value of chest CT for predicting breast tumor size using pathology measurements as reference standards.MethodsTumor sizes (defined as greatest diameter) were retrospectively measured on the preoperative chest CT images of 285 patients with surgically proven unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…Like Ahn et al, 13 we found that smaller tumors ( 2 cm/pT1) had a higher concordance rate as compared to larger tumors (>2 cm/! pT2).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Like Ahn et al, 13 we found that smaller tumors ( 2 cm/pT1) had a higher concordance rate as compared to larger tumors (>2 cm/! pT2).…”
Section: Discussionsupporting
confidence: 82%
“…[3][4][5][6][7][8][9] Few studies compared pathologic tumor size to radiologic size using different radiologic modalities. [11][12][13][14][15][16][17][18] In a recent study, Yoo et al 11 studied the correlation of MRI and pathologic size in breast carcinomas. However, not every breast carcinoma patient gets an MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordance between MRI and pathologic diameter was defined as a tumor size difference of 0.5 cm. This is because limits within which measurements on MRI are considered concordant with measurements at pathology vary and are in the range of 0-2 cm (3,7,(11)(12)(13)(14)(15)(16); however, the majority of previous studies that classified concordance defined a diameter difference of 0.5 cm as concordant. Disease was considered to be overestimated if the size of the tumor on MRI was > 0.5 cm larger than the pathologic tumor size.…”
Section: Image Analysismentioning
confidence: 99%
“…Micro-CT is a new imaging modality with a remarkable spatial resolution of 50-1 mm. While a prior study has shown the efficacy of chest CT in determining primary tumour size in breast cancer, 28 micro-CT had not been previously assessed for its accuracy in measuring primary tumour size. This study aimed to assess the accuracy of intraoperative micro-CT in measuring primary breast tumour size within lumpectomy specimens.…”
Section: Discussionmentioning
confidence: 99%